Anticoagulation Therapy in Patients With Coronavirus Disease 2019: Results From a Multicenter International Prospective Registry (Health Outcome Predictive Evaluation for Corona Virus Disease 2019 [HOPE-COVID19]). Issue 6 (2nd April 2021) - Santoro, Francesco; Núñez-Gil, Ivan J.; Viana-Llamas, María C.; Maroun Eid, Charbel; Romero, Rodolfo; Fernández Rozas, Inmaculada; Aparisi, Alvaro; Becerra-Muñoz, Victor Manuel; García Aguado, Marcos; Huang, Jia; Maltese, Ludovica; Cerrato, Enrico; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : OBJECTIVES: No standard therapy, including anticoagulation regimens, is currently recommended for coronavirus disease 2019. Aim of this study was to evaluate the efficacy of anticoagulation in coronavirus disease 2019 hospitalized patients and its impact on survival. DESIGN: Multicenter international prospective registry (Health Outcome Predictive Evaluation for Corona Virus Disease 2019). SETTING: Hospitalized patients with coronavirus disease 2019. PATIENTS: Five thousand eight hundred thirty-eight consecutive coronavirus disease 2019 patients. INTERVENTIONS: Anticoagulation therapy, including prophylactic and therapeutic regimens, was obtained for each patient. MEASUREMENTS AND MAIN RESULTS: Five thousand four hundred eighty patients (94%) did not receive any anticoagulation before hospitalization. Two-thousand six-hundred one patients (44%) during hospitalization received anticoagulation therapy and it was not associated with better survival rate (81% vs 81%; p = 0.94) but with higher risk of bleeding (2.7% vs 1.8%; p = 0.03). Among patients admitted with respiratory failure (49%, n = 2, 859, including 391 and 583 patients requiring invasive and noninvasive ventilation, respectively), anticoagulation started during hospitalization was associated with lower mortality rates (32% vs 42%; p < 0.01) and nonsignificant higher risk of bleeding (3.4% vs 2.7%; p = 0.3). Anticoagulation therapy was associated with lower mortality rates in patients treated with invasive ventilation (53% vs 64%; p = 0.05) without increased rates of bleeding (9% vs 8%; p = 0.88) but not in those with noninvasive ventilation (35% vs 38%; p = 0.40). At multivariate Cox' analysis mortality relative risk with anticoagulation was 0.58 (95% CI, 0.49–0.67) in patients admitted with respiratory failure, 0.50 (95% CI, 0.49–0.67) in those requiring invasive ventilation, 0.72 (95% CI, 0.51–1.01) in noninvasive ventilation. CONCLUSIONS: Anticoagulation therapy in general population with coronavirus disease 2019 was not associated with better survival rates but with higher bleeding risk. Better results were observed in patients admitted with respiratory failure and requiring invasive ventilation.